(untitled) - Pilbeam, Susan P. (St. Louis, 1998)
Textbook for respiratory therapy students covering ventilator care. Chapters include an outline, learning objectives, review questions, and references.
Keywords: Respiratory therapy,Respirators (Medical equipment),Artificial respiration,Respiration, Artificial,Respiration Disorders,Ventilators, Mechanical,Điều trị bệnh về đường hô hấp,Máy hô hấp nhân tạo (Thiết bị y tế),Hô hấp, nhân tạo,Rối loạn hô hấp,Máy hô hấp nhân tạo, Máy móc; therapy,Trị liệu